2019
DOI: 10.1002/ese3.268
|View full text |Cite
|
Sign up to set email alerts
|

Test and study on transfusion law of gas in mining coal

Abstract: In this paper, the seepage tests of mining coal were conducted by servo‐controlled seepage apparatus. These tests consist of conventional triaxial compression seepage tests, and load and unload seepage tests. It was observed that the peak strength and corresponding axial strain of raw coal samples gradually increase with the increase of confining pressure, which conforms to the Mogi‐Coulomb strength criterion, and the internal friction angle was calculated as φ = 42.65°, and the cohesion force was c = 3.56 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Different range values of gray corresponded to specific components: fissure, coal matrix, and mineral from low gray to high gray. The image segmentation, which combined the Gray Average Processing method and the U-Net model in the ORS Dragonfly 4.1, was used to extract and reconstitute different components of coal, as discussed in more detail in our previous study (Zhang et al, 2019). A sampleÕs CT image processing, pre-processing, and 3D reconstitution are illustrated in Figure 9.…”
Section: Ct Images Processing and 3d Reconstitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different range values of gray corresponded to specific components: fissure, coal matrix, and mineral from low gray to high gray. The image segmentation, which combined the Gray Average Processing method and the U-Net model in the ORS Dragonfly 4.1, was used to extract and reconstitute different components of coal, as discussed in more detail in our previous study (Zhang et al, 2019). A sampleÕs CT image processing, pre-processing, and 3D reconstitution are illustrated in Figure 9.…”
Section: Ct Images Processing and 3d Reconstitutionmentioning
confidence: 99%
“…The behavioral changes of coal in the stress field-fracture field-seepage field from the perspective of multi-field coupling were analyzed and provided a theoretical and experimental basis for related research. Zhang et al (2019) studied the evolution of coal permeability under the influence of mining face and found that, under the same confining pressure, the ultimate strength of a coal sample after a loading-unloading test was significantly lower than after the triaxial compression test, while its permeability increased. By simplifying the actual mining stress path, Yin et al (2015) carried out experiments with axial pressure loading and confining pressure unloading of coal samples based on the standard triaxial compression equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that, in the initial stage of loading and unloading, the permeability of the intact coal body weakens; when the stress difference exceeds the yield strength of the coal sample, the fracture volume increases, resulting in capacity expansion and permeability enhancement of the coal sample. Guo et al [17] found that the cyclic loading and unloading could cause damage to the intact coal body; the permeability of the coal sample is enhanced when the stress exceeds its yield strength; as peak stress rises and damage in the coal sample accumulates, the stress sensitivity of the intact coal body gradually decreases. Cheng et al [18] designed mining stress paths for three stages (loading, unloading and recovery), according to different stress concentration coefficients.…”
Section: Introductionmentioning
confidence: 99%